Analisis Jual Beli Melalui Facebook Marketplace Prespektif Maqhasid Syariah di Surabaya - AINI, UMI QURROTUL; FAGEH, ACHMAD (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to analyze buying and selling practices via Facebook Marketplace in Surabaya from a Maqashid Syariah perspective. Maqashid Syariah are sharia goals designed to achieve benefit and prevent harm for humanity, with a focus on five main aspects: protecting religion (Hifz al-Din), protecting the soul (Hifz al-Nafs), protecting reason (Hifz al- 'Aql), guarding offspring (Hifz al-Nasl), and guarding wealth (Hifz al-Mal). The research used is field research using qualitative methods. Meanwhile, data collection techniques use documentation and interviews. The data analysis used is inductive analysis, namely a data analysis method that presents specific empirical facts which are then drawn into a general explanation. The results of the research show that although the majority of products sold on Facebook Marketplace meet halal criteria and comply with sharia principles. , there are still challenges regarding user security from fraud, accuracy of product information, and secure payment mechanisms